Shared-learning experience during a clinical pharmacy practice experience - Zakaria, Syahiera Farhana; Awaisu, Ahmed (2011)

(untitled)
Purpose of Study: To implement a shared learning approach through fourth-year students’ mentorship of third-year students and to assess the perception of the mentored students on the value of their shared learning experience.